Comparing Class II MHC DRB3 Diversity in Colombian Simmental and Simbrah Cattle Across Worldwide Bovine Populations - Ordoñez, Diego; Bohórquez, Michel David; Avendaño, Catalina; Patarroyo, Manuel Alfonso (Frontiers in Genetics, 2022)
The major histocompatibility complex (MHC) exerts great influence on responses to infectious diseases and vaccination due to its fundamental role in the adaptive immune system. Knowledge about MHC polymorphism distribution among breeds can provide insights into cattle evolution and diversification as well as population-based immune response variability, thus guiding further studies. Colombian Simmental and Simbrah cattle’s BoLA-DRB3 genetic diversity was compared to that of taurine and zebuine breeds worldwide to estimate functional diversity. High allele richness was observed for Simmental and Simbrah cattle; nevertheless, high homozygosity was associated with individual low sequence variability in both the β1 domain and the peptide binding region (PBR), thereby implying reduced MHC-presented peptide repertoire size. There were strong signals of positive selection acting on BoLA-DRB3 in all populations, some of which were poorly structured and displayed common alleles accounting for their high genetic similarity. PBR sequence correlation analysis suggested that, except for a few populations exhibiting some divergence at PBR, global diversity regarding potential MHC-presented peptide repertoire could be similar for the cattle populations analyzed here, which points to the retention of functional diversity in spite of the selective pressures imposed by breeding.